2006
DOI: 10.1128/jb.188.8.2983-2992.2006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of BrpA on Critical Virulence Attributes ofStreptococcus mutans

Abstract: Streptococcus mutans, the primary etiological agent of human dental caries, has developed multiple mechanisms to colonize and form biofilms on the tooth surface. The brpA gene codes for a predicted surfaceassociated protein with apparent roles in biofilm formation, autolysis, and cell division. In this study, we used two models to further characterize the biofilm-forming characteristics of a BrpA-deficient mutant, strain TW14. Compared to those of the parent strain, UA159, TW14 formed long chains and sparse mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
183
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(199 citation statements)
references
References 40 publications
16
183
0
Order By: Relevance
“…mutans can also function as a transcriptional regulator (Bitoun et al, 2012a(Bitoun et al, , 2013Wen et al, 2006). Previous studies showed that deficiency of BrpA caused substantial alterations in the transcriptional profile of the deficient mutant, including changes in transcripts involved in peptidoglycan biosynthesis, DNA repair and stress tolerance response, and biofilm formation (Bitoun et al, 2012a(Bitoun et al, , 2013Wen et al, 2006). Consistent with our previous findings that BrpA is a key regulator of the acid tolerance response in Strep.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…mutans can also function as a transcriptional regulator (Bitoun et al, 2012a(Bitoun et al, , 2013Wen et al, 2006). Previous studies showed that deficiency of BrpA caused substantial alterations in the transcriptional profile of the deficient mutant, including changes in transcripts involved in peptidoglycan biosynthesis, DNA repair and stress tolerance response, and biofilm formation (Bitoun et al, 2012a(Bitoun et al, , 2013Wen et al, 2006). Consistent with our previous findings that BrpA is a key regulator of the acid tolerance response in Strep.…”
Section: Discussionsupporting
confidence: 80%
“…Like several members of the LCP proteins (Hanson et al, 2011(Hanson et al, , 2012Lazarevic et al, 1992), BrpA in Strep. mutans can also function as a transcriptional regulator (Bitoun et al, 2012a(Bitoun et al, , 2013Wen et al, 2006). Previous studies showed that deficiency of BrpA caused substantial alterations in the transcriptional profile of the deficient mutant, including changes in transcripts involved in peptidoglycan biosynthesis, DNA repair and stress tolerance response, and biofilm formation (Bitoun et al, 2012a(Bitoun et al, , 2013Wen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations